FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Vidyarto Nugroho; Nicholas Nicholas (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2020)
The purpose of this research is to analyze the effect of leverage, liquidity, firm size,and firm age oncompanies financial performance in property and real estate companies listed on Indonesia Stock Exchange in 2015 – 2017. The sampling method used purposive sampling with total sample 105 data which was financial statement from www.idx.co.id. The collected data were analyzed by using Eviews 10. The research result that independent variables describe the dependent variable up to 72.54% , while 27.46% is described by other factors. Independent variable leverage, firm size, and firm age do not have a significant effect on firm value, while the liquidity have a significant effect on companies financial performance.